Falsafah Hidup Orang Tidung Perspektif Pemikiran Islam: Studi Tentang Adat Kebiasaan Suku Tidung Nunukan - Jeri Saputra Jeri; Muhammad Imam Syafi’i; Mukhlis Ansori Harahap; Muhammad Yusril (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2025)
Indonesia’s cultural heritage has become an interesting study to date. History, intellectual system, economy and culture in the past have become a wealth of Indonesia that cannot be aeasily studied. The study of Islamic treasures in Indonesia still often focuses on the regions of Sumatra, Java and their surroundings. Meanwhile, in the Kalimantan region it is still rarely done. One of the treasures of Islam in Kalimantan that we can find is Tidung. Tidung is a native ethincity of Kalimantan which is part of the Dayak, but what distinguishes them is the belief they adhere to. Tidung is also interseting to study regarding the ulun pagun phenomenon as a dealetic of a new Islamic identify. This research seeks to explain about Nunukan Regency, Tidung and the costums of the Tidung tribe, especially in Nunukan Regency.